موارد ومناهج الماوردي في كتابه أدب الدنيا والدين - العتابي، ضياء رزاق خلاوي (الجامعة المستنصرية - كلية التربية الأساسية, 2022)
إن نشأة الماوردي ونبوغه تنبئ على أنه منحدر من عائلة علمية جليلة فضلا عن نبوغ أخيه الذي لم تذكر المصادر اسمه، وان استيطان الماوردي مدينة بغداد التي كانت قبلة العلم والعلماء، جعل منه أحد جهابذة العلم، وذلك عن طريق العلماء الذين اخذ عنهم وسمع منهم في تلك المدينة العظيمة وتنوعه في التأليف والتصنيف جعل من طلبة العلم قصده والعكوف على درسه وحضور حلقة خطبه، وذلك للاستفادة منه والأخذ عنه، وكان لنبوغه المعرفي وتضلعه في علوما كثيرة جعل من العلماء منحه لقب "قاضي القضاة" الذي اكتسبه ولازمه حتى وفاته، ثم بعد ذلك لقب به القضاة من بعده فيعد كتاب أدب "الدنيا والدين" من الكتب الرائعة في بابه، إذ أخذ به الماوردي بتعريف الغوامض وشرح المفردات وغير ذلك وجعله على أبواب خمس كل باب منها مباحثها الخاصة بها، والكتاب لا يخلو من نظرات فلسفية واجتماعية واقتصادية فضلا عن الموضوعات الإسلامية الخاصة بالأخلاق الدينية الإسلامية القائمة على الكتاب والسنة وتبين أن الماوردي نهج بهذا الكتاب عدة مناهج وهي إشارات على تضلعه وتطلعه وأسلوبه في تلك الحقبة وما كان يمتاز به فضلا عن تنوع مواضيع الكتاب جعلت من الماوردي أن يتنوع بموارده واقتباساته، وهذا ما أمتاز به هذا الكتاب، إذ نجد أن هناك كثيرا من المصادر والموارد التي اعتمد عليها الماوردي سواء بشكل مباشر مصرحا بذلك، أم بشكل غير مباشر وبدون تصريح. Al-Mawardi’s upbringing and brilliance were indicated that he descended from a distinguished scholarly family, as well as the brilliance of his brother, whose name the sources did not mention. The great city and its diversity in authorship and classification made the students of knowledge his intention and to devote themselves to his studies and attend his sermons, in order to benefit from it and take from it, and his brilliance of knowledge and his mastery of many sciences made scholars give him the title of “Qadi al-Qadat” which he acquired and required him until his death, and then after that the title It was used by judges after him, and he considered the book “Adab al-Dunya wa al-Din” among the wonderful books in its chapter, as al-Mawardi took it by defining the mysteries and explaining the vocabulary and so on and made it into five chapters, each chapter having its own investigations, and the book is not devoid of philosophical, social and economic views as well as special Islamic topics Islamic religious morals based on the Qur’an and the Sunnah, and it was found that Al-Mawardi approached this book with several approaches, which are indications of his versatility, aspiration, and style in that era and what was distinguished by him, in addition to the diversity of the topics of the book, which made Al-Mawardi to diversify With its resources and quotations, and this is what distinguishes this book, as we find that there are many sources and resources that Al-Mawardi relied on, whether directly authorized to do so, or indirectly and without authorization.
Keywords: الماوردي، علي بن محمد بن حبيب، ت. 450 هـ. -- الأدب العربي -- الأخلاق الإسلامية -- الوعظ والإرشاد -- النقد الأدبي